Вариативность приставок в русских видовых парах: некоторые дополнения к теме - Olsson Gustaf (Russian Federation, 2022)
The topic of this article is prefix variation in Russian aspectual pairs, i.e. cases where an unprefixed, imperfective verb has two or more perfective correlates, formed by different prefixes. The first part of the article gives an overview of different manifestations of prefix variation discussed in earlier linguistic literature: semantic differences, stylistic differences and diachronic language change.
The second part of the article is concerned with prefix variation in aspectual pairs of new loan verbs, which is a rather under studied manifestation of prefix variation in Russian. The second part also contains a co-occurrence study of one recently borrowed verb, šerit ́ ‘to share’, and three candidates for being perfective correlates: zašerit ́, pošerit ́ and rasšerit ́. The analysis of these verbs is based on texts from Russian language media, gathered from the mass media database Integrum. It shows that rasšerit ́ is used exclusively in contexts referring to sharing that takes place on the internet, as seen in examples like rasšerit ́ video ‘share a video’ and rasšerit ́ ssylku ‘share a link’. The two other verbs – zašerit ́ and pošerit ́ – are used in a wider range of contexts; in addition to sharing links, videos, pictures et c. on the internet, these two verbs can also refer to sharing concrete things in real life. These meanings are visible in examples like pošerit ́ sčyot ‘share the bill’, pošerit ́ podarok ‘share a gift’ and zašerit ́ taksi ‘share a taxi’. These and similar contexts are not found for rasšerit ́.
I argue that prefixes in Russian aspectual pairs are never semantically “empty”, or “purely aspectual”. Instead, the meaning of the prefix overlaps with the meaning of the verb in prefixed aspectual pairs, which creates an illusion of the prefix be ing semantically “empty”. This phenomenon is known under different names: “overlap hypothesis” or “Vey–Schooneveld effect”. The overlap in meaning between verb and prefix is very clear in the case of rasšerit ́: the prototypical, spatial meaning of the prefix raz- is ‘movement in different directions’, which harmonizes well with the meaning ‘share file [on the internet]’ of the base verb šerit ́ and implies that the shared file reaches many different internet users. The prefixes po- and za-, on the other hand, have a broader range of meanings and a more abstract semantic scope: po- implies that the action takes place during a short time, and za- is very productive in loan verbs overall, most often in verbs with a resultant meaning. As a result, the verbs zašerit ́ and pošerit ́ are used in a broader range of meanings than rasšerit ́.